2014
DOI: 10.1103/physrevd.89.065030
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Lorentz-violating action

Abstract: We demonstrate the generation of the three-dimensional Chern-Simons-like Lorentz-breaking ``mixed" quadratic action via an appropriate Lorentz-breaking coupling of vector and scalar fields to the spinor field and study some features of the scalar QED with such a term. We show that the same term emerges through a nonpertubative method, namely the Julia-Toulouse approach of condensation of charges and defects.Comment: 12 pages, accepted to PR

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…We demonstrated explicitly that in this case, one can generate a nonlocal generalization of the electrodynamics whose action is an infinite series in derivatives, so that one has, besides of the usual Maxwell term, also the Podolsky term, and higher-order terms. We showed explicitly that the Podolsky term can be generated as a quantum correction as well being finite, so, we can see that perturbative and non-perturbative approaches for obtaining new terms are equivalent in a certain sense as it has been claimed in [7]. Actually, we demonstrated that the Julia-Toulouse approach opens broad possibilities for obtaining new effective theories with higher-derivative operators.…”
Section: Comments and Conclusionsupporting
confidence: 63%
See 1 more Smart Citation
“…We demonstrated explicitly that in this case, one can generate a nonlocal generalization of the electrodynamics whose action is an infinite series in derivatives, so that one has, besides of the usual Maxwell term, also the Podolsky term, and higher-order terms. We showed explicitly that the Podolsky term can be generated as a quantum correction as well being finite, so, we can see that perturbative and non-perturbative approaches for obtaining new terms are equivalent in a certain sense as it has been claimed in [7]. Actually, we demonstrated that the Julia-Toulouse approach opens broad possibilities for obtaining new effective theories with higher-derivative operators.…”
Section: Comments and Conclusionsupporting
confidence: 63%
“…The dual of the charge condensation described here is the dilution of the equivalent defects (vortices) in the superconductor. Meaning that if the vortices dilute (and charge condensation occurs), the system becomes a perfect superconductor as in (7) or if the vortices condensate (and charge dilution takes place) we recover the free Maxwell theory. As it is known, the superconductivity phase of a material can be destroyed by proliferation of vortices, and, as it is shown in [8], the picture presented here, describes this scenario.…”
Section: Phase Transition and The Condensation Of Topological Defmentioning
confidence: 85%
“…Although the majority of studies of Lorentz violating field theories is developed in a fourdimensional spacetime, there are considerable interest in the description of three-dimensional (3D) ones [11][12][13]. Besides the algebraic richness of odd dimensional spacetimes, one may say that the most appealing aspect of 3D field theories is the UV finiteness in some models.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the condensation of topological defects constitutes a mass gap generation mechanism whose general signature is the so-called "rank jump phenomenon": a massless Abelian p-form describing the system in the phase with diluted defects gives place to a new effective massive (p + 1)-form describing the system in the condensed phase. Quevedo and Trugenberger refer to this as the "Julia-Toulouse mechanism" (JTM) and, more recently, some of us generalized the JTM in various aspects and applied it to many different physical systems [31][32][33][34][35][36][37][38][39][40][41].…”
Section: Jhep07(2015)070mentioning
confidence: 99%